Průmysl sociálního vyloučení: Lokalita Janov - Michal Tošner; Zuzana Poláková; Nikola Indrová; Matěj Novák; Viktor Rumpík; Klára Židlická (AntropoWebzin)
The article argues that we should study social exclusion not only in one particular locality, but rather through a multi-sited approach, which would take into account the various sites of the directing system (in governmental and non-governmental organization) and the labor market in one field of research, as these sites are integral parts of the complex situation of social exclusion. The article thus focuses on both the economical and social aspects of services in social policy and on their impact on everyday lives of the people in the locality. It further discusses the governmental organizations themselves, their practices, concepts and outcomes as well as the NGOs and their practices and concepts. The article concludes with the finding that the situation of ‘social exclusion’ increases the employment opportunities in the social services for the middle-class actors (in both branches: governmental and non-governmental sphere), however, these are ineffective in their attempts to include the ‘socially excluded’. Furthermore, the occurrence of socially and economically disadvantaged actors is abused in practices of the illegal jobs by employers in the area, and entails loss of taxes and public finances. This consequently constitutes a complex mechanism of sustainable inequality, which we called the industry of social exclusion.